PENGARUH KELOMPOK REFERENSI, KELUARGA DAN KOMUNIKASI PEMASARAN TERHADAP KEPUTUSAN MAHASISWA DALAM MEMILIH PERGURUAN TINGGI UNIVERSITAS MUSAMUS MERAUKE - Tarsisius Kana (Universitas Musamus,Merauke,Papua, 2014)
The research aimed to examine the impact of the reference, family and marketing communication groups to wardsthe students’ decision in choosing Musamus University Higher Education.This was a descriptive research by using 100 samples carried out in cluster. The research used the techniques of an observation, an interview, and a questionnaire in collecting data. The data were analysed by using the quantitative analysis through the multiple linear regression analysis with the SPSS version 20.0 program.The research result indicates that simultaneously the reference, family, marketing communication groups have the positive and significant impact towards the students’ decision in choosing Musamus University Higher Education. Partially, the reference group dominantly has the positive and significant impact on the students’ decision. The families have the positive and significant impact on the students’ decision. The marketing communication does not have the positive and significant impact on the students’ decision.